2014
DOI: 10.1111/lam.12268
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation in 24-well plates is an efficient screening platform for filamentous fungi

Abstract: Significance and Impact of the Study: Fermentation studies with filamentous fungi and especially screening experiments often struggle with high inter-vessel variations in metabolite production. This study compares two different types of frequently used screening methods namely batch fermentation in Erlenmeyer flasks with batch fermentation in 24-well plates. The results demonstrate that the variance potentially can be reduced two and a half-fold using 24-well plates leading to improved resolution when testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Fermentation setup in 24-well plates was made following the principles of Linde et al [28] and citric acid production medium from [38] …”
Section: Fermentation Setup and Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fermentation setup in 24-well plates was made following the principles of Linde et al [28] and citric acid production medium from [38] …”
Section: Fermentation Setup and Conditionsmentioning
confidence: 99%
“…When LaeA was deleted in A. carbonarius the production of ochratoxin, a potential human carcinogen, was decreased with 68-97 % compared to wild type and the production of conidia in light and in dark was decreased as well [9]. A. carbonarius is closely related to A. niger [1] and similarly to A. niger it produces citric acid in high amounts when cultivated at optimal conditions [28,49].…”
Section: Introductionmentioning
confidence: 95%
“…When a large number of strains or cultivation conditions have to be tested, a high throughput screening (HTS) system is required, which can yield reproducible and scalable results. In order to increase throughput compared to traditional shake flasks, miniaturization of cultivations by microtiter plates or microbioreactors is desired [35]. HTS of filamentous fungi in microtiter plates is a challenging task because (a) there is a substantial risk of cross-contamination between individual cultivations, (b) highly viscous fermentation broth can cause oxygen transfer limitation and local inhomogeneity, and (c) excessive wall growth may take place, which favors sporulation.…”
Section: Introductionmentioning
confidence: 99%
“…Galactaric acid production by T. reesei has previously been demonstrated in flask cultures [8], but at much lower concentrations than can be obtained in bioreactors [7]. Running and Bansal [12] demonstrated that 24-well plates can have as good or better oxygen transfer as shaken flasks, depending on the shaking regime applied, and 24-well plates are increasingly being used for the cultivation of filamentous fungi [1315]. It is therefore useful to assess whether galactaric acid production by T. reesei could be scaled down for production in 24-well plates using pectin as substrate.…”
Section: Introductionmentioning
confidence: 99%